2014
DOI: 10.1016/j.actaastro.2014.02.021
|View full text |Cite
|
Sign up to set email alerts
|

High-fidelity numerical simulation of complex dynamics of tethered spacecraft

Abstract: a b s t r a c tThis paper presents an analytical model and a geometric numerical integrator for a tethered spacecraft model that is composed of two rigid bodies connected by an elastic tether. This high-fidelity model includes important dynamic characteristics of tethered spacecraft in orbit, namely the nonlinear coupling among tether deformations, rigid body rotational dynamics, a reeling mechanism, and orbital dynamics. A geometric numerical integrator, referred to as a Lie group variational integrator, is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…By preserving certain mathematical structures and conservation laws from the continuous into the discrete domain, such discretization schemes allow for better qualitative representation of the system and accurate energy and momentum simulation for exponentially long times even for larger discrete time steps [12]. For this reason, they have often been used to reduce the computational cost of simulations and optimal control strategies and could be of great benefit for fuel and energy optimization problems ( [14], [15], [16], [17]). In Section IV we present how such models can readily be used in the proposed optimizationbased scheme and show that their characteristics can be employed to simultaneously reduce the number of constraints and guarantee structure-preserving properties of the resulting solution.…”
Section: Introductionmentioning
confidence: 99%
“…By preserving certain mathematical structures and conservation laws from the continuous into the discrete domain, such discretization schemes allow for better qualitative representation of the system and accurate energy and momentum simulation for exponentially long times even for larger discrete time steps [12]. For this reason, they have often been used to reduce the computational cost of simulations and optimal control strategies and could be of great benefit for fuel and energy optimization problems ( [14], [15], [16], [17]). In Section IV we present how such models can readily be used in the proposed optimizationbased scheme and show that their characteristics can be employed to simultaneously reduce the number of constraints and guarantee structure-preserving properties of the resulting solution.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important issues in the spacecraft design is the attitude control [6]. Several analytic and numerical models for tethered spacecraft have been developed [7, 8]. Over last four decades, the design of a reliable, autonomous and highly accurate formation control strategy for multiple spacecraft has been the subject of many research efforts [9].…”
Section: Introductionmentioning
confidence: 99%
“…French et al [28] have shown that the effect of adding tether mass and elasticity in their continuum tether model did not make a significant impact on the performance of an asteroid mitigation system. The recent study of Lee et al [29] included a reeling mechanism in their high fidelity model of two rigid bodies connected by an elastic tether. The reeling mechanism captured the coupling interaction between the tether reeling and rotational dynamics.…”
Section: Introductionmentioning
confidence: 99%